Socially responsible management and good practice - Berezyanko, Tamara; Sheremet, Oleg; Halytsia, Ihor; Zienina-Bilichenko, Antonina; Marshalenko, Marianna (My University, 2022)
The relevance of the study is due to the need for a detailed research of the impact of socially responsible management and good practice on the performance of small, medium and large enterprises. In this regard, this article aims to identify the relationship between socially responsible management, good practice and economic growth of enterprises; the purpose of this study is to analyse and assess the impact of socially responsible management and good practice on various performance indicators of enterprises. Achieving this purpose requires solving a number of tasks, the content of which reflects the sequence of research stages: to study the theoretical and methodological aspects of the impact of socially responsible management and good practice on performance indicators of enterprises; to analyse the main world trends in the application of socially responsible management and good practice; to study the experience of advanced countries in the implementation of socially responsible management; to develop methodological approaches to assessing the impact of socially responsible management and good practice on the performance of enterprises; to develop a set of proposals for attracting socially responsible management methods for government bodies. The leading method to study this problem is the method of systems analysis which was used to study the idea of socially responsible management as a complex multicomponent structure that should be involved and operate in an unstable political and economic situation. The process of writing this article also involved such research methods as the method of logical analysis, comparative analysis, methods of synthesis and deduction, the method of classification, the method of surveying respondents. The article presents the results of the study in tables and figures that reflect the levels of application of socially responsible management methods, their impact and advantages; internal and external stakeholders in the company's activities; components of balanced socially responsible management; survey results of respondents. The article materials are of practical value for entrepreneurs, managers, teachers and students in the field of management and human relations.

Актуальність дослідження зумовлена ​​необхідністю детального дослідження впливу соціально відповідального менеджменту та належної практики на результативність діяльності малих, середніх та великих підприємств. У зв’язку з цим дана стаття спрямована на виявлення взаємозв’язку між соціально відповідальним управлінням, передовою практикою та економічним зростанням підприємств; Метою цього дослідження є аналіз та оцінка впливу соціально відповідального менеджменту та належної практики на різні показники діяльності підприємств. Досягнення поставленої мети потребує вирішення низки завдань, зміст яких відображає послідовність етапів дослідження: вивчити теоретико-методологічні аспекти впливу соціально відповідального менеджменту та належної практики на показники діяльності підприємств; проаналізувати основні світові тенденції застосування соціально відповідального менеджменту та належної практики; вивчити досвід передових країн щодо впровадження соціально відповідального господарювання; розробити методичні підходи до оцінки впливу соціально відповідального менеджменту та належної практики на результати діяльності підприємств; розробити пакет пропозицій щодо залучення соціально відповідальних методів управління для органів влади. Провідним методом дослідження даної проблеми є метод системного аналізу, який використовувався для вивчення ідеї соціально відповідального менеджменту як складної багатокомпонентної структури, яка має бути задіяна та діяти в умовах нестабільної політичної та економічної ситуації. У процесі написання статті також були задіяні такі методи дослідження, як метод логічного аналізу, порівняльний аналіз, методи синтезу та дедукції, метод класифікації, метод опитування респондентів. У статті подано результати дослідження в таблицях і малюнках, які відображають рівні застосування методів соціально відповідального управління, їх вплив і переваги; внутрішні та зовнішні стейкхолдери в діяльності компанії; складові збалансованого соціально відповідального господарювання; результати опитування респондентів. Матеріали статті мають практичне значення для підприємців, менеджерів, викладачів та студентів у сфері менеджменту та людських відносин.
Keywords: корпоративна соціальна відповідальність; corporate social responsibility; методи відповідального управління; methods of responsible management; відповідальна трудова практика; responsible labor practices; стейкхолдери; stakeholders; опитування (анкетування); surveys (questionnaires); кафедра економіки праці та менеджменту